2003
DOI: 10.1097/00001756-200310060-00016
|View full text |Cite
|
Sign up to set email alerts
|

Identification and distribution of aspartoacylase in the postnatal rat brain

Abstract: Aspartoacylase metabolizes N-acetylaspartic acid to produce L-aspartate and acetate. An aspartoacylase deficiency in humans is responsible for Canavan disease, a lethal autosomal recessive leukodystrophy. The role of aspartoacylase in the mammalian brain is unclear. Here we have generated and characterized a highly specific polyclonal antibody against aspartoacylase which recognizes a 37 kDa monomer and a dimer in normal but not in aspartoacylase-deficient rat tissue. Aspartoacylase protein expression sharply … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
47
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 23 publications
6
47
0
Order By: Relevance
“…et al, 1973;Kirmani et al, 2003) becomes critical in order to liberate the acetate from NAA for the synthesis of acetyl CoA, which is necessary for the synthesis of certain myelin-associated lipids. A number of studies, including the recent demonstrations of the selective localization of ASPA in oligodendrocytes in the CNS Kirmani et al, 2002;Klugmann et al, 2003;Madhavarao et al, 2004), and the increasing NAA concentrations observed by MRS in human fetuses in utero during development (Girard et al, 2005) are consistent with the acetate-deficiency hypothesis of Canavan disease.…”
Section: Naa Breakdown and Myelin Lipid Synthesismentioning
confidence: 68%
See 1 more Smart Citation
“…et al, 1973;Kirmani et al, 2003) becomes critical in order to liberate the acetate from NAA for the synthesis of acetyl CoA, which is necessary for the synthesis of certain myelin-associated lipids. A number of studies, including the recent demonstrations of the selective localization of ASPA in oligodendrocytes in the CNS Kirmani et al, 2002;Klugmann et al, 2003;Madhavarao et al, 2004), and the increasing NAA concentrations observed by MRS in human fetuses in utero during development (Girard et al, 2005) are consistent with the acetate-deficiency hypothesis of Canavan disease.…”
Section: Naa Breakdown and Myelin Lipid Synthesismentioning
confidence: 68%
“…Immunohistochemical studies using polyclonal antibodies to ASPA confirmed that it was expressed in oligodendrocytes (Klugmann et al, 2003). Further, using dual-labeling immunohistochemistry it has been shown that ASPA is definitely expressed strongly in oligodendrocytes in the CNS, but that it is not expressed in astrocytes .…”
Section: Naa Catabolismmentioning
confidence: 80%
“…Since oligodendrocytes are an important source of CNS ASPA (Bhakoo et al, 2001), if not the most important (Baslow et al, 1999;Kirmani et al, 2002;2003;Klugmann et al, 2003;Mhadavarao et al, 2002;, repopulation of the brain of a CD patient with functional oligodendrocytes could potentially rectify much of the disease phenotype through the restoration of normal NAA metabolism. Neural stem cells have been successfully used to generate oligodendrocytes in the CD mouse model (Surendran et al, 2004) and these oligodendrocytes expressed a myelin-specific enzyme indicative of myelin-producing ability, but clinical outcomes of such a…”
Section: Cell Therapymentioning
confidence: 99%
“…ASPA is predominantly localized to white matter. 10,11 The mechanism by which NAA leaves neurons is not known, although it is likely that transport into oligodendrocytes occurs via the sodium-dependent carboxylate transporter, NaC3. 12,13 The turnover of NAA in the brain is relatively slow, with a half-life of ∼7 h.…”
Section: Pathways and Roles Of Naamentioning
confidence: 99%